2020
DOI: 10.1155/2020/8812019
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Pretrained Convolutional Neural Networks for Tomato Leaf Disease Detection

Abstract: Vegetable and fruit plants facilitate around 7.5 billion people around the globe, playing a crucial role in sustaining life on the planet. The rapid increase in the use of chemicals such as fungicides and bactericides to curtail plant diseases is causing negative effects on the agro-ecosystem. The high scale prevalence of diseases in crops affects the production quantity and quality. Solving the problem of early identification/diagnosis of diseases by exploiting a quick and consistent reliable method will bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…The training loss decreases linearly from epoch to epoch but the validation loss oscillates up and down initially and it was very high and gradually declines. Tomato leaf disease detection using optimized pre trained convolutional neural network is conducted (20) using two types of datasets which are collected from the real field in uncontrolled environment then augmented to maximize the number of datasets used for the experiment and public dataset collected from controlled environment which is a real world representation . In this experiment authors have proved to be more challenging for pre trained network models.…”
Section: Resultsmentioning
confidence: 99%
“…The training loss decreases linearly from epoch to epoch but the validation loss oscillates up and down initially and it was very high and gradually declines. Tomato leaf disease detection using optimized pre trained convolutional neural network is conducted (20) using two types of datasets which are collected from the real field in uncontrolled environment then augmented to maximize the number of datasets used for the experiment and public dataset collected from controlled environment which is a real world representation . In this experiment authors have proved to be more challenging for pre trained network models.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent past machine learning applications have seen widespread use in various domains [51,52]. However, there is limited work to evaluate the usability aspect of machine learning applications [53].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmad et al [54] used four different pretraining convolution neural networks VGG19, VGG16, ResNet, and Inception V3, and the models were trained by fine-tuning parameters. The experimental results showed that the Inception V3 had the best performance on the two datasets(the laboratory dataset and the field dataset).…”
Section: A Leaf Disease Detection By Well-known Deep Learning Architectures 1) Classic Deep Learning Architectures For Leaf-disease Detecmentioning
confidence: 99%